MERTI SENDANG, MEMULIAKAN SUMBER AIR DENGAN PENDEKATAN KEBUDAYAAN - Raharjo, Pamuji (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This research aims to look at traditional practices that are still part of the culture of the people of Bleberan Village in Gunungkidul Regency. The existence of the